Themes et esthetique verbale du panegyrique asante: le cas des bardes de Manhyia - Mensah, Magdalene (2011)
A dissertation presented to the Faculty of Social Sciences in partial fulfilment of the requirements for the Master of Arts (Comparative Literature) degree.